Long chain fatty acids alter the interactive binding of ligands to the two principal drug binding sites of human serum albumin - Yamasaki, K.; Hyodo, S.; Taguchi, K.; Nishi, K.; Yamaotsu, N.; Hirono, S.; Chuang, Victor; Seo, H.; Maruyama, T.; Otagiri, M. (Public Library of Science, 2017)
A wide variety of drugs bind to human serum albumin (HSA) at its two principal sites, namely site I and site II. A number of reports indicate that drug binding to these two binding sites are not completely independent, and that interactions between ligands of these two discrete sites can play a role. In this study, the effect of the binding of long-chain fatty acids on the interactive binding between dansyl-L-asparagine (DNSA; site I ligand) and ibuprofen (site II ligand) at pH6.5 was examined. Binding experiments showed that the binding of sodium oleate (Ole) to HSA induces conformational changes in the molecule, which, in turn, changes the individual binding of DNSA and ibuprofen, as well as the mode of interaction between these two ligands from a 'competitive-like' allosteric interaction in the case of the defatted HSA conformer to a 'nearly independent' binding in the case of non-defatted HSA conformer. Circular dichroism measurements indicated that ibuprofen and Ole are likely to modify the spatial orientation of DNSA at its binding site. Docking simulations suggest that the long-distance electric repulsion between DNSA and ibuprofen on defatted HSA contributes to a 'competitive-like' allosteric interaction, whereas extending the distance between ligands and/or increasing the flexibility or size of the DNSA binding site in fatted HSA evokes a change in the interaction mode to 'nearly independent' binding. The present findings provide further insights into the structural dynamics of HSA upon the binding of fatty acids, and its effects on drug binding and drug-drug interactions that occur on HSA.